2020
DOI: 10.1111/dth.13754
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoedematous striae: An undescribed entity

Abstract: Striae are one of the common and unsightly cutaneous adverse drug reactions of long-term application of topical steroids. 1 Striae rubra, striae alba, striae atrophicans, striae distensae, striae nigra, and striae cearulea are documented in English dermatology literature. The most common variants striae rubra and striae alba are commonly seen in the groin, flanks, abdomen, proximal thighs, breasts (in females), and axillae. Common causes for formation of striae include physiological

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Frequently seen consequences of misuse of potent topical steroids include striae rubra, striae albae, hypopigmentation, telangiectasias, thinning of the skin, and extensive tinea [ 57 ]. Striae can also ulcerate or appear edematous [ 58 , 59 ].…”
Section: Abuse Of Topical Glucocorticoids and The Emergence Of ...mentioning
confidence: 99%
“…Frequently seen consequences of misuse of potent topical steroids include striae rubra, striae albae, hypopigmentation, telangiectasias, thinning of the skin, and extensive tinea [ 57 ]. Striae can also ulcerate or appear edematous [ 58 , 59 ].…”
Section: Abuse Of Topical Glucocorticoids and The Emergence Of ...mentioning
confidence: 99%
“…Some striae assume a pseudoedematous appearance [Figure 25]. 68 Others may continue to grow despite the patient having stopped applying fixed-dose combinations. This is indicative of high potency topical steroids having a depot effect.…”
Section: Signs Of Topical/injectable Corticosteroid Use and Irritant mentioning
confidence: 99%
“…Study concluded 20% azelaic acid applied two times every day may be superior to HQ 4% in decreasing mild Melasma [28]. Few of the related studies were reviewed [29][30][31][32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%